A geometric approach to correlation inequalities in the plane - Figalli, Alessio; Maggi, Francesco; Pratelli, Aldo (Annales de l'Institut Henri Poincaré - Probabilités Et Statistiques, 2014)
By elementary geometric arguments, correlation inequalities for radially symmetric probability measures are proved in the plane. Precisely, it is shown that the correlation ratio for pairs of width-decreasing sets is minimized within the class of infinite strips. Since open convex sets which are symmetric with respect to the origin turn out to be width-decreasing sets, Pitt's Gaussian correlation inequality (the two-dimensional case of the long-standing Gaussian correlation conjecture) is derived as a corollary, and it is in fact extended to a wide class of radially symmetric measures.
Keywords: Correlation inequalities; Gaussian correlation conjecture; Radially symmetric measures